An NIR‐Fluorophore‐Based Theranostic for Selective Initiation of Tumor Pyroptosis‐Induced Immunotherapy. Issue 36 (29th July 2021) - Wang, Kewei; Xiao, Xuan; Jiang, Maolin; Li, Jisi; Zhou, Jielian; Yuan, Youyong
Abstract: Pyroptosis is an inflammatory form of programmed cell death that can effectively eliminate malignant cells and boost anticancer immunity. However, most of the current pyroptosis inducers lack cell selectivity, which may cause severe side effects for cancer therapy. In this work, for the first time, the authors discovered that the commonly used near‐infrared (NIR) fluorogenic hemicyanine (CyNH2 ) induces pyrolysis to kill cancer cells and boost antitumor immunity. Cancer cells overexpressing the NAD(P)H: quinone oxidoreductase isozyme 1 (NQO1)‐responsive theranostic (NCyNH2 ) are designed for selective cell pyroptosis and are nonfluorescent with low toxicity before activation. In the presence of NQO1, the fluorescence of CyNH2 is restored and can selectively initiate pyroptosis of cancer cells and further lead to systemic antitumor immunity activation for solid tumor therapy. Thus, this fluorogenic NIR dye may represent a novel theranostic agent for the selective initiation of tumor pyroptosis. Abstract : Herein, it is discovered that the near‐infrared (NIR) fluorogenic hemicyanine (CyNH2 ) induces pyrolysis to kill cancer cells and boost antitumor immunity for the first time. Cancer cells overexpressing the NAD(P)H: quinone oxidoreductase isozyme 1 (NQO1)‐responsive theranostic (NCyNH2 ) were designed for selective cell pyroptosis. Thus, this fluorogenic NIR dye represents a novel theranostic agent for the selective initiation of tumor pyroptosis.